A NEW CLINICAL SIGN IN MENINGITIS-JAMIL'S SIGN - Jamil, Shahid; Raza, Syed Shahmeer; Khan, Sohrab; Jamil, Mashal (Journal of Ayub Medical College Abbottabad, 2022)
Background: This study explored a new clinical sign in meningitis: neck stiffness in lateral position, also known as Jamil's sign. Methods: A patient was placed in the left lateral position. The examiner held the patient's occiput with his left hand and the chin with his right hand. Then, the examiner performed a manoeuvre by fully extending and then fully flexing the neck. By doing so, the examiner was able to get ample time and range of movement to judge the tone. The tone was assessed during flexion and extension. If the examiner felt resistance, rigidity, or stiffness while performing this manoeuvre, Jamil's sign was present. Otherwise, it was supple, and Jamil's sign was absent. Results: Of the 419 patients, Jamil's sign was present in 362 patients and absent in 57 patients. Upon lumbar puncture, 361 patients had meningitis, and 58 patients did not have meningitis. Among patients with meningitis, Jamil's sign was present in 357 patients and absent in four patients. Jamil's sign had a sensitivity of 98.89% and a specificity of 91.38%. Conclusion: Due to its high sensitivity and specificity for the diagnosis of meningitis, Jamil's sign obviates the need for unnecessary lumbar puncture, which is performed in doubtful situations of neck stiffness in the supine position